2005
DOI: 10.1183/09031936.05.00049704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosiglitazone and 15-deoxy- 12,14-prostaglandin J2 on bleomycin-induced lung injury

Abstract: Thiazolidinedione rosiglitazone and 15-deoxy-D 12,14 -prostaglandin J 2 (15d-PGJ 2 ), are two peroxisome proliferator-activated receptor (PPAR)-c ligands. The aim of this study was to investigate the effect of rosiglitazone and 15d-PGJ 2 on the lung injury caused by bleomycin administration.Mice subjected to intratracheal administration of bleomycin developed significant lung injury. An increase in immunoreactivity to nitrotyrosine, poly(ADP ribose) polymerase (PARP) and inducible nitric oxide synthase as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 41 publications
6
109
0
Order By: Relevance
“…PPARγ, the master switch of lipogenic differentiation in preadipocytes as well as mesenchymal stem cells, is also involved in lipofibroblast formation (Rehan and Torday, 2012) and PPARγ agonists have been shown to protect mice from developing fibrosis Genovese et al, 2005). Furthermore, adiponectin, which is a direct transcriptional target for PPARγ, has shown a similar effect in primary culture of skin fibroblasts isolated from scleroderma patients .…”
Section: Discussionmentioning
confidence: 67%
“…PPARγ, the master switch of lipogenic differentiation in preadipocytes as well as mesenchymal stem cells, is also involved in lipofibroblast formation (Rehan and Torday, 2012) and PPARγ agonists have been shown to protect mice from developing fibrosis Genovese et al, 2005). Furthermore, adiponectin, which is a direct transcriptional target for PPARγ, has shown a similar effect in primary culture of skin fibroblasts isolated from scleroderma patients .…”
Section: Discussionmentioning
confidence: 67%
“…42,43 Genovese and coworkers reported that neutrophil infiltration of the lung was significantly reduced by PPAR-c agonists in the course of bleomycin-induced mouse lung injury. 44 Also, in a murine in vivo model of LPS-induced airway inflammation it was shown by Birrell and colleagues that the TZD rosiglitazone but not dexamethasone reduced the neutrophil number in the lung tissue when administered after the LPS insult. 45 Interestingly, when we added PPAR-c agonists directly or 12 hr post-RSV-infection we still observed a down-regulation of ICAM-1 on RSV-infected A549 cells similar to the data presented in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…PPARg ligands also have antifibrogenic potential in murine airways. For example, administration of thiazolidinediones or 15d-PGJ 2 inhibited bleomycin-induced pulmonary injury and fibrosis in mice (33,76). PPARg agonists are postulated to act through cell cycle arrest and TGF-b1 inhibition for myofibroblast differentiation and collagen deposition (76,77).…”
Section: Discussionmentioning
confidence: 99%
“…The dose was chosen based on previous publications in which PPARg was efficiently induced in the lung (32,33). The last injection was done 24 hours before the end of the designated inhalation exposure period.…”
Section: Administration Of a Pparg Agonist 15d-pgjmentioning
confidence: 99%